TMC1 and TMC2 Proteins Are Pore-Forming Subunits of Mechanosensitive Ion Channels - Jia, Yanyan; Zhao, Yimeng; Kusakizako, Tsukasa; Wang, Yao; Pan, Chengfang; Zhang, Yuwei; Nureki, Osamu; Hattori, Motoyuki; Yan, Zhiqiang (Neuron (Cambridge, Mass.), 2020)
Transmembrane channel-like (TMC) 1 and 2 are required for the mechanotransduction of mouse inner ear hair cells and localize to the site of mechanotransduction in mouse hair cell stereocilia. However, it remains unclear whether TMC1 and TMC2 are indeed ion channels and whether they can sense mechanical force directly. Here we express TMC1 from the green sea turtle (CmTMC1) and TMC2 from the budgerigar (MuTMC2) in insect cells, purify and reconstitute the proteins, and show that liposome-reconstituted CmTMC1 and MuTMC2 proteins possess ion channel activity. Furthermore, by applying pressure to proteoliposomes, we demonstrate that both CmTMC1 and MuTMC2 proteins can indeed respond to mechanical stimuli. In addition, CmTMC1 mutants corresponding to human hearing loss mutants exhibit reduced or no ion channel activity. Taken together, our results show that the CmTMC1 and MuTMC2 proteins are pore-forming subunits of mechanosensitive ion channels, supporting TMC1 and TMC2 as hair cell transduction channels.